A Novel Design of Chaos Based S-Box Using Difference Distribution Table (CD S-Box) - Khan, M.A. (Springer Verlag, 2014)
This research work reports the design methodology of a novel chaotic substitution box that is dynamically designed by systematically optimizing using DDT. DDT is a tool that helps in differential cryptanalysis of S-box. The proposed S-box shows very low differential probability as compared to other chaos based deigned S-box recently, while maintaining good cryptographic properties and linear approximation probability. Our proposed CD S-box achieves very low differential approximation probability of 8/256. Â© Springer-Verlag Berlin Heidelberg 2014.